Plasma lipid peroxidation and antioxidant levels in patients with rheumatoid arthritis - Kamanli, A; Naziroglu, M; Aydilek, N; Hacievhyagil, C (Wiley, 2004)
In recent years, a great number of studies have investigated the possible role of reactive oxygen species in the aetiology and pathogenesis of rheumatoid arthritis (RA). The aim of this study was to investigate plasma concentrations of vitamin E, betacarotene, activities of glutathione peroxidase (GSH-Px) and catalase, levels of lipid peroxidation (MDA) and reduced glutathione (GSH) in 36 patients with rheumatoid arthritis (RA) and 22 healthy age-matched controls. The plasma activity of GSH-Px and catalase (p < 0.001), levels of GSH (p < 0.01), concentration of beta-carotene (p < 0.05) and vitamin E (p < 0.001), haemoglobin and hematocrit (p < 0.05) were significantly lower in patients with RA than in controls. The MDA levels (p < 0.01), C reactive protein, rheumatoid factor, anti-streptolysin-o values (p < 0.001), platelet count (p < 0.05) and erythrocyte sedimentation rate (p < 0.001) were higher in the patient group than in the control group. These results provide some evidence for a potential role of increased lipid peroxidation and decreased enzymic and non-enzymic antioxidants in RA by its inflammatory character. These results suggested that oxidant stress plays a very important role in the pathogenesis of RA. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: antioxidants; lipid peroxidation; vitamin E; catalase; rheumatoid arthritis